طر التدريس عبر الاءنترنت لدى محاضري اللغة العربية في الكلية الاءسلامية بملقا (KUIM) خلال فترة قرار قيود الحركة في ماليزيا - Fahmi Bin Md Fisol
The Arabic teaching method during Covid-19 Pandemic has changed from face-to-face between lecturers and students in a classrooms or halls to the online teaching in front of phones or computers by using the internet, technology or any existing teaching platform. This study was conducted to reveal the online teaching methods for Arabic language lecturers at the Melaka Islamic University College (KUIM) and their perceptions about teaching effectiveness using this modern technology. This is quantitative and qualitative study using an exploratory descriptive approach through questionnaires distributed to ten Arabic language lecturers at KUIM. This study aims to find out the online teaching methods used during the period of the Movement Control Order (MCO) in Malaysia due to Covid-19. The results of the study found several things among them; the lecturers use the online platform to teach Arabic which has never been done before and and they are found to be positive and very fond of this online teaching method. In addition, the lecturers found that the level of understanding of students through online learning is moderate.